Kewenangan Perusahaan Finance Dalam Melakukan Eksekusi Jaminan Fidusia Perspektif Hukum Islam - Masning Nur Azizah (Journal of Islamic Business Law, 2017)
This research aims to clarify the authority of PT Amana Finance in Malang execution and fiduciary assurance describes the view of Islāmic law against authority PT. Amana Finance Malang in executing the fiduciary guarantee. A guarantee of financing, financing the many agencies that do the financing with a fiduciary guarantee. One example of a case, there is a financing institution that should have a duty to register the object fiduciary guarantee, but not listed as well in terms of execution. The financing agencies unilaterally undertake the execution of the object of the guarantee. This research is the empirical juridical, using the a statutory and conceptual research approach. The data sources are used the primary data, secondary data, and tertiary data. Data collection is done with the interview and documentation. Interviewees in this study was Mr. Ghazali as a responsible company and Lily as staff administration. The results of this research show that PT. Amana Finance Malang is not authorized to conduct the execution directly against a fiduciary guarantee of the objects, but rather keep it through the applicable rules in accordance with title execution. And based on the Islāmic law execution conducted by PT. Amana Finance Malang is invalid, because it is supposed to be a procedure that is done is with the process of awarding letter warning beforehand is not by doing a direct execution. Keyword: Execution; Fiduciary Guarantee; Islamic Law